The Study of Factors Related for Healthy-Breakfast Consumption Behavior of Community Public Heath Student in Faculty of Science, Lampang Rajabhat University - Wongsa, Kotchakorn; Meunpirom, Montira; Choothong, Chisapath (Journal of The Royal Thai Army Nurses, 2022)
This research was a cross-sectional research. The objectives of this research were to study the relationship between personal factors, knowledge, attitude and healthy-breakfast consumption behavior of Community Public Health students, Faculty of Science Lampang Rajabhat University. Research sample was 53 Community Public Health students were selected by purposive sampling. Research instrument was the questionnaire that pass validity, quality checked and reliability. Data were analyzed by using descriptive statistics and inferential statistics to find the relationship of the research factors. The results of the study showed that knowledge, attitude and healthy-breakfast consumption behavior of community public health students were at a moderate level. After testing the relation, were found that the height range was positively correlated with the knowledge of healthy-breakfast consumption (r s = .34, p < .05), weight range and body mass index were positively correlated with the attitudes towards healthy-breakfast consumption at low level (rs = .32, r = .34, p < .05), the period of time for having breakfast was negatively correlated with the healthy-breakfast consumption behavior at low level (rs = - .41, p < .05).